PEMANTAUAN DAN EVALUASI PELAKSANAAN PROGRAM STBM DIWILAYAH KERJA PUSKESMAS JAWAKISA KECAMATAN AESESA SELATAN KABUPATEN NAGEKEOPROPINSI NUSA TENGGARA TIMUR - Delfina Benga; Suhartono Suhartono; Nur Endah Wahyuningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Community-Based Total Sanitation (STBM) is an approach to promoting hygiene and sanitation behaviors by stimulating communities. During the 8 years of STBM activity in Southern Aesesa Subdistrict last year there were 4 villages that had already reached the ODF (Open Defecation Free) villages of a total of 7 villages. The study aims to evaluate the implementation of a Community-based Total Sanitation program in Southern Aesesa Subdistrict that includes input, process and output stages. This study uses an evaluation method with a qualitative approach. The sampling technique was purposive sampling. The number of samples in this study were 20 people. The results showed that there is only one sanitarian officer, no transportation facilities, and no cross-sectoral evaluation, but there is an increase in the availability of Community-Based Total Sanitation facilities. The conclusion of this study is that the implementation of the STBM program in the work area of the Jawakisa Health Center has not been able to run well because there are several obstacles in its implementation. It is hoped that there will be assistance and participation from the Nagekeo District Health Office in the implementation of the STBM program. Keywords: Evaluation, Community-based total sanitation, qualitative